2004
DOI: 10.1109/tbme.2004.828037
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact Method for Sleep Stage Estimation

Abstract: This paper describes a novel method to estimate sleep stage through noninvasive and unrestrained means. The Rechtschaffen and Kales (R-K) method is a standard to estimate sleep stage. However, it involves restraining the examinee and, thus, induces psychological stress. Furthermore, it requires specialists with a high degree of technical expertise and the use of an expensive polygraph. The sleep estimation method presented here is based on the noninvasive and unrestrained pneumatic biomeasurement method presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 9 publications
1
65
0
Order By: Relevance
“…Previous studies on the estimation of sleep condition using heart rate reported approximately 83% NonREM consistency [18], and 92% SWS consistency [19]. It is difficult to compare the estimation accuracy between our method and previous studies using heart rate (HR), since these earlier reports tested adults.…”
Section: Evaluation Methods Of the Estimated Resultsmentioning
confidence: 79%
“…Previous studies on the estimation of sleep condition using heart rate reported approximately 83% NonREM consistency [18], and 92% SWS consistency [19]. It is difficult to compare the estimation accuracy between our method and previous studies using heart rate (HR), since these earlier reports tested adults.…”
Section: Evaluation Methods Of the Estimated Resultsmentioning
confidence: 79%
“…Information about environmental conditions is relevant in all types of exercises and stages of the therapy. Biosignals such as heart rate variability, EEG, muscle tension, skin conductance, movement, and respiration give important information about the degree of relaxation, and about sleep and sleep stages [44,46]. In the future, automated snoring detection may be of great value in the alignment phase.…”
Section: Ubiquity and Mobile Devices In Cbt-imentioning
confidence: 99%
“…REM sleep / NREM sleep) cannot be determined from the data. More recently, researchers have focused on measuring heart/pulse rate and analyzing its variability: HRV (Watanabe, 2004, Michimori, 2003and Wakuda, 2007. The sleep stages can be calculated from HRV if the indices of HRV are properly mapped for the sleep stages.…”
Section: Related Workmentioning
confidence: 99%